Effect of Self-Care Education Based on Virtual Networks on Quality of Life in HIV-Positive Patients - Anna Amini; Akram Peyman; Monireh Hatami (Hamadan University of Medical Sciences, 2020)
Aims: Given the prevalence of AIDS and the need to enhance self-care programs and improve quality of life, the aim of the present study was to determine the effect of self-care education based on virtual networks on quality of life in HIV-positive patients. Materials & Methods: This clinical trial was conducted on HIV positive patients referred to the Counseling Centers for Behavioral Disorders in Tehran in 2019 and 80 people of them who were eligible for the study were selected by multistage random sampling method and randomly assigned into control and intervention groups (40 people in each group). Data were collected using demographic information questionnaire and the Multidimensional Quality of Life Questionnaire for Persons with HIV/AIDS (MQoL-HIV) which were completed before the training and two weeks after the last training session. Data analysis was performed using SPSS 19 software. Findings: At the beginning of the study, the mean scores of quality of life and its ten domains did not have significant difference (p>0.05); but after the intervention a significant difference was observed in the mean scores of quality of life and its domains except the domains of cognitive function, economic, interact with the spouse and sexual function (p<0.05). Conclusions: The self-care education programs based on virtual networks are effective on promoting the quality of life of HIV-positive patients.